A Loan Word in the Noble Qur'an - Andri Purwanto (Scope : Journal of English Language Teaching, 2018)
The objective of this research is to analyze the Islamic terms according translation theories. One of the translation theories is modifying a loan word with meaning components, i.e. form, additions, couplets, synonim, comparison, and the last is a classifier. This theory is introduced by Larson in dealing with cultural and biblical terms.This research is a library research and the source data is taken from the Noble Qur’an, English translation and commentary translated by Dr Muhammad Taqi-ud-Din Al-Hilali dan Dr Muhammad Muhsin Khan. The research discusses some translation theories, i.e. (1) a loan with features of form, (2) a loan word with function, (3) a loan word with form and function, (4) a loan word with a comparison, (5) a loan word with a classifier, (6) a loan word with couplets, triplets, quadruplets and quintaplets, (7) a loan word with a synonim, and (8) a loan word with a a synonim plus reference, (9) a loan word with no modification.